DISTRIBUSI BETA WEIBULL UNTUK ANALISIS DATA SURVIVAL - , VINIE FRANCISCA; , Rianti Siswi Utami, S.Si., M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This study explains about the parameter estimation of the beta Weibull distribution model. Beta Weibull distribution is a result of the distribution modification between the beta function and Weibull distribution which have four parameters. Beta Weibull distribution has several specific submodels of several parameters which are bathtup, unimodal, increasing, and decreasing. For estimating the parameter of beta Weibull distribution model, it is used the likelihood mazimum method and BFGS. It shows that beta Weibull distribution is better than Weibull distribution.